Angle of attack impact in the aerothermodynamics of a hypersonic vehicle with surface discontinuity-like a cavity - Daimer Mauthsud Leovan Ospina Contreras (2017)
The study described in this dissertation was undertaken with the purpose to investigate the impact of discontinuities present on the surface of hypersonic space vehicles. With this perspective in mind, computational simulations of a non-reacting rarefied hypersonic flow over a flat plate with a cavity have been performed by using the Direct Simulation Monte Carlo method. Simulations provided a comprehensive description about the nature of the flowfield structure and the aerodynamic surface properties on the cavity resulting from changes in the length-to-depth (L/H) ratio and changes in the angle of attack of the oncoming flow. A detailed description of the flowfield properties (velocity, density, pressure and temperature) and aerodynamics surface properties (number flux, heat transfer, pressure and skin friction) were obtained by a numerical method that properly account for non-equilibrium effects in the transition flow regime. Results for a cavity defined by L/H ratio of 1, 2, 3 and 4, and flow with angle of attack of 10, 15 and 20 degrees, were compared to those of a flat plate without a cavity with zero-degree angle of incidence and with a flat plate at incidence. The analysis showed that the flow topology inside the cavity, composed by recirculation regions, depended on the L/H ratio as well as on the angle of attack, for the conditions investigated. For L/H < 3 a single vortex core was formed, and filled entirely the cavity. In contrast, for L/H of 3 and 4, two vortices were formed inside the cavity, at the vicinity of the backward and forward faces. The analysis also showed that, for the L/H = 4 case, the flow topology inside the cavity corresponds to that of a ${''}$closed cavity${''}$ in the continuum flow regime for 10-degree angle of incidence, and similar to an open cavity for the others angles of attack investigated. In addition, it was found that the maximum values for the heat transfer, pressure and skin friction coefficients inside the cavity took place on the cavity forward face. It was also found that, maximum values for heat transfer coefficient inside the cavities increased with increasing the angle of attack $α$. However, it was observed that these maximum values are smaller than those observed in a flat-plate without a cavity for the corresponding angle of attack. Consequently, in terms of pressure, the presence of the cavity on the vehicle surface can not be ignored in the vehicle design.